Immune Checkpoint Inhibitor–Mediated Aseptic Meningitis and Hypophysitis - Pavel Bleik; Panisara Fangsaard; Nataliya Yuklyaeva (Case Reports in Oncological Medicine)
Immune checkpoint inhibitors have revolutionized cancer treatment, yet their use is associated with unique and sometimes unpredictable immune-related adverse events. We present a case of a 67-year-old female with renal cell cancer treated with ipilimumab and nivolumab who developed aseptic meningitis and hypophysitis. This case highlights the challenges in managing immune-related adverse events and underscores the need for vigilance in monitoring patients receiving ICIs.